The university teacher and appropriated evaluation practices in higher education: a student's perspective - Maura Maria Morita Vasconcellos; Claudia Chueire de Oliveira; Neusi Aparecida Berbel; Corina Maria Tedeschi Busnardo (Faculdade de Medicina de Botucatu (Unesp), 2007)
This article is the result of an investigation done in the preservice teaching education courses at Londrina State University (UEL), which tried to understand evaluation practices of university teachers working in those courses nominated by students as good evaluators. The study included semi-structured interviews with 48 teachers, recorded and transcripted for treatment and qualitative analysis. One of the main aspects was to observe personal aspects which stimulate the evaluation practice in higher education, focusing on the teachers personal experiences, self-evaluation, and the reflective process on their teaching practice. The values and conceptions which embody the evaluation practice were also investigated. The main objective of the research was to extract lessons from the positive practice of the evaluation for university teachers in general. Some of the noteworthy lessons included: the assumption of a comprehensive conception on teaching which surpasses the limits of the classroom itself, the self-evaluation as a continuous process of the evaluators practice, and the predominance of the objectives over the procedures in the evaluation process.